The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1152/jappl.1992.72.4.1493
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle responses to lower limb suspension in humans

Abstract: Eight subjects participated in a 6-wk unilateral lower limb suspension (ULLS) study to determine the influence of reduced weight bearing on human skeletal muscle morphology. The right shoe was outfitted with a platform sole that prevented the left foot from bearing weight while walking with crutches, yet it allowed freedom of movement about the ankle, knee, and hip. Magnetic resonance images pre- and post-ULLS showed that thigh muscle cross-sectional area (CSA) decreased (P less than 0.05) 12% in the suspended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

32
150
5

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(187 citation statements)
references
References 19 publications
32
150
5
Order By: Relevance
“…Muscle weakness following immobilization by a full‐length leg cast was mainly due to the marked decrease in the maximum voluntary force (neurogenic muscle activation) rather than loss of TMV 43. This mechanism is supported by the consistent observation that the loss of voluntary muscle strength is greater than that of muscle cross‐sectional area 44, 45. Muscle strength recovered in a similar manner in both the bimagrumab and placebo groups, seemingly independent of the rate and magnitude of TMV changes.…”
Section: Discussionmentioning
confidence: 88%
“…Muscle weakness following immobilization by a full‐length leg cast was mainly due to the marked decrease in the maximum voluntary force (neurogenic muscle activation) rather than loss of TMV 43. This mechanism is supported by the consistent observation that the loss of voluntary muscle strength is greater than that of muscle cross‐sectional area 44, 45. Muscle strength recovered in a similar manner in both the bimagrumab and placebo groups, seemingly independent of the rate and magnitude of TMV changes.…”
Section: Discussionmentioning
confidence: 88%
“…23,24 For example, knee extensor muscle CSA was reduced by 14% following 6 weeks of bed rest, 23 and the thigh muscle CSA decreased 12% after 6 weeks of unilateral lower limb suspension. 24 The magnitude of skeletal muscle atrophy reported in this study indicates that incomplete SCI could evoke greater disuse than previous reported models of microgravity. Furthermore, skeletal muscle atrophy was even more pronounced by 6% after correcting for IMF.…”
Section: Discussionmentioning
confidence: 98%
“…Previously, MRI was used to quantify skeletal muscle response to unloading and after SCI. [1][2][3][4]23,24 The accuracy of MRI versus dual-energy X-ray absorptiometery (DEXA) in determining skeletal muscle atrophy has been previously investigated showing that DEXA overestimates the proportion of the muscle in fat-free mass after SCI and inaccurately reflects the degree of muscle atrophy compared to MRI. 3 MRI also provides the advantage over computed tomography (CT) by facilitating the acquisition of multiple slices over a single slice commonly used in CT scans, which can inaccurately represent the exact changes in muscle size in response to training or disuse.…”
Section: Discussionmentioning
confidence: 99%
“…The subjects were highly motivated, and all had prior experience with knee-extension MVC. We have previously established that the VL muscle constitutes roughly 30% of the total quadriceps group cross-sectional area (28). Accordingly, electrical current sufficient to elicit ϳ30% of the observed isometric knee-extension MVC was determined and used for the subsequent EMS protocol in the AB subjects.…”
Section: Subjectsmentioning
confidence: 99%
“…Muscle samples were obtained from all subjects immediately before the initial stimulation and 24 h after the second stimulation bout. Biopsies were taken from the VL by using the percutaneous biopsy technique, as done previously (16,28). Samples were immediately cooled with liquid nitrogen and then stored at Ϫ70°C until analyzed.…”
Section: Subjectsmentioning
confidence: 99%